â€œRANCANG BANGUN KENDALI PERALATAN RUMAH TANGGA BERBASIS SMARTPHONE ANDROIDâ€. - taufik akbar; Indra Gunawan; Khairil Anwar (Infotek: Jurnal Informatika dan Teknologi, 2020)
So far, the community in general can control lights or other electronic equipment with just a switch, but the control is limited by distance. Therefore, the construction of an electronic equipment control system application prototype was built on the Android platform as a new alternative solution for remote control. The application built on the Android platform has an attractive and easy to understand user interface. In addition, the control system built utilizes a Bluetooth network for sending control instructions to Arduino. In this prototype using Arduino Uno as a processor, Android as a control, Bluetooth HC-06 module as Arduino communication with Android and using relay as a control switch with 4 channel specifications. Communication between an android smartphone and a microcontroller can be done wirelessly using Bluetooth, which the Android smartphone and Bluetooth module on the microcontroller system can communicate using serial data. The speech recognition feature on an Android smartphone can be used to control the lights using voice commands. This is done by initializing the spectrum of voice commands in the form of strings into character codes that have been identified by the microcontroller. Control of electronic equipment will not work if the Android smartphone is out of range of the Bluetooth wireless transmission range of the Bluetooth module because the Bluetooth connection will be disconnected automatically.DOI : 10.29408/jit.v3i2.2348